Joe Celko’s SQL for smarties : - Celko, Joe (Morgan Kaufmann, 2005)
In the SQL database community, Joe Celko is a well-known columnist and purveyor of valuable insights. In Joe Celko's SQL for Smarties: Advanced SQL Programming, he picks up where basic SQL training and experience leaves many database professionals and offers tips, techniques, and explanations that help readers extend their capabilities to top-tier SQL programming.